PENGARUH PELATIHAN DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN (Studi Kasus PT. Wahana Prestasi Logistik Kota Bekasi) - Sri Lestari; Abdul Viqri (Aliansi : Jurnal Manajemen dan Bisnis, 2019)
This study aims to examine the effect of variables with the title “The Effect of Training and Work Discipline on Employee Performance at PT. Wahana Logistics Achievement in Bekasi City”. This research was conducted on employees at PT Wahana Prestasi Logistik in the city of Bekasi. The sample used was 60 predetermined employees. Hypothesis testing uses validity and reliability test, regression analysis, correlation, determination coefficient, t test and f test by first testing classic assumptions. Based on the results of data analysis and discussion, the training variable partially (XI) has a positive and significant effect on employee performance (Y) where t count = 4.598 is greater t-table = 1.672 which means H0 is rejected while H1 is accepted. Work discipline variables (X2) partially have a positive and significant effect on employee performance (Y), where t-count = 2.720 is greater t-table = 1.672 which means H0 is rejected while H1 is accepted. Simultaneously obtained the results of F-count 22,392 F-table which is equal to = 3.16 which means that H0 is rejected and H1 is accepted, meaning that training variables and work discipline simultaneously have a positive and significant effect on employee performance. The determination coefficient of 44% is explained by training and work discipline while the rest is explained by other factors outside the research variable.